Material Selection for Unmanned Aerial Vehicles (UAVs) Wings Using Ashby Indices Integrated with Grey Relation Analysis Approach Based on Weighted Entropy for Ranking (Journal of Engineering, 2023)
The designer must find the optimum match between the object's technical and economic needs and the performance and production requirements of the various material options when choosing material for an engineering application. This study proposes an integrated (hybrid) strategy for selecting the optimal material for an engineering design depending on design requirements. The primary objective is to determine the best candidate material for the drone wings based on Ashby's performance indices and then rank the result using a grey relational technique with the entropy weight method. Aluminum alloys, titanium alloys, composites, and wood have been suggested as suitable materials for manufacturing drone wings. The requirements for designing a drone's wings are to make them as light as possible while meeting the stiffness, strength, and fracture toughness criteria. The conclusion indicates that Carbon Fiber-Reinforced Polymer (CFRP) is the best material for producing drone wings. In contrast, wood and aluminum alloys were the cheapest materials when the design had to be inexpensive.